Empirical Model for Measuring How Corporate Sustainability Performance Affects Customer Attraction and Economic Success - Obioha, Emmanuel Obinali; Klingelhöfer, Heinz Eckart (Indonesian Journal of Sustainability Accounting and Management, 2025)
The focus of the paper is to test a model that measures how corporate sustainability performance (i.e. socio-economic and environmental dimensions) affect economic success via customer attraction. Quantitative data was collected from companies constituting the Socially Responsible Investment (SRI) index at the Johannesburg Stock Exchange. Factor analysis was used for data reduction, Chi-square tests for the association between two categorical variables and Cronbach alpha for validity and reliability. The methodology was two-fold: testing the linkages between corporate sustainability dimensions, customer attraction and economic success, and putting them together to form an integrated model. The results confirm a positive link between corporate socio-economic and environmental performance (i.e. the development of socio-economic aspects and human rights as well as a focus on environmental processes and products), customer attraction and economic success. The model provides a comprehensive approach that management can use to investigate corporate sustainability performance drivers and to obtain a clearer understanding of the impacts of corporate decisions regarding the economic success of both the company and the society. The value of the study is to provide organisations insights on how to achieve competitive advantage and improve economic success.